The Mineral Question: How Energy and Technology Will Determine the Future of Mining - Bardi, Ugo (Frontiers in Energy Research, 2013)
Almost 150 years after that Jevons (1866) published his paper “The Coal Question” a debate on mineral depletion has been ongoing between two main schools of thought: one that sees depletion as an important problem for the near future and another that sees technology and human ingenuity as making depletion only a problem for the remote future. Today, however, we have created intellectual tools that permit us to frame the problem on the basis of physical factors, in particular on the basis of thermodynamics. The present paper examines the problem of mineral depletion from a broad viewpoint, with a specific view on the role of energy in the mining and production processes. The conclusion is that energy is a fundamental factor in determining how long we can expect the supply of mineral resources to last at the present prices and production levels. The rapid depletion of our main energy resources, fossil fuels, is creating a serious supply problem that is already being felt in terms of high prices of all mineral commodities. Technology can mitigate the problem, but not solve it. In a non-remote future, the world’s industrial system will have to undergo fundamental changes in order to adapt to a reduced supply of mineral commodities.